PEMBELAJARAN DALAM MENINGKATKAN KEMAMPUAN BAHASA ANAK USIA 5-6 TAHUN DALAM MASA PANDEMI DI TK KRISTEN KAISAREA - Bali, Engelbertus Nggalu; Menoh, Vilda Yulinda; Saba, Khetye; Koten, Angelikus Nama (Universitas Nusa Cendana, 2023)
Caesarea Christian Kindergarten experiences many obstacles in the implementation of learning, that is, not all the material that the teacher sends is understandable to children, there are parents who work together so that children do not do the assignments given so that these obstacles can affect children's developmental achievements, especially children's language development. The purpose of this study was to find out the learning that was carried out by teachers to improve the language skills of children aged 5-6 years during the Covid-19 pandemic. This research is located at the Christian Kindergarten of Caesarea Kupang. The subjects in this study were teachers at the Christian Kindergarten of Caesarea Kupang. This type of research is qualitative research, data collection techniques used are interviews, observation and documentation. Data and research results that have been collected are then analyzed descriptively. From the results of learning research in order to improve the language skills of children aged 5-6 years in Caesarea Christian Kindergarten, the implementation of learning still has opening, core and closing activities. each activity is made as simple as possible so that parents can guide their children properly and there is coordination with the teacher so that they can find out about the child's development so that the teacher makes home visits to each child once or twice a week.